2016
DOI: 10.1016/j.joca.2015.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent cyclic mechanical tension promotes endplate cartilage degeneration via canonical Wnt signaling pathway and E-cadherin/β-catenin complex cross-talk

Abstract: ICMT promotes endplate cartilage degeneration via activation of Wnt/β-catenin signaling and suppression of physical protein-protein interactions between E-cadherin and β-catenin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 51 publications
3
40
0
Order By: Relevance
“…Furthermore, SW improves joint function, reduces inflammatory cytokines which are responsible for osteoarthritic degeneration and enhances the recovery effects 13 . Recently, three clinical studies support the potential therapeutic utility of SW in the treatment of OA [21][22][23] .IL-10 inhibits the synthesis of different pro-inflammatory cytokines (IFN-γ, IL-2, IL-3, TNF-α and GM-CSF) which are hyper-expressed in arthritic conditions. The overexpression of N-Cadherin and β-Catenin is associated with degeneration diseases 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SW improves joint function, reduces inflammatory cytokines which are responsible for osteoarthritic degeneration and enhances the recovery effects 13 . Recently, three clinical studies support the potential therapeutic utility of SW in the treatment of OA [21][22][23] .IL-10 inhibits the synthesis of different pro-inflammatory cytokines (IFN-γ, IL-2, IL-3, TNF-α and GM-CSF) which are hyper-expressed in arthritic conditions. The overexpression of N-Cadherin and β-Catenin is associated with degeneration diseases 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocyte‐produced catabolic factors include TNF‐α, IL‐1, IL‐6, IL‐8, matrix metalloproteinases (MMPs), and a disintegrin and metalloproteinase with thrombospondin motifs family members (ADAMTSs) . Increasing evidence also demonstrates that chondrocytes exhibit a self‐defense mechanism that entails increasing anabolic activity in response to pathological processes, including the increased release of growth factors (i.e., BMP‐2, Wnt) and synthesis of type II collagen and other extracellular matrix proteins . This suggests that, although chondrocytes undergo a self‐protective mechanism, the elevation of anabolic molecules is not sufficient to neutralize upregulation of catabolic molecules, including TNF‐α, under pathological conditions.…”
Section: Pgrn In Osteoarthritismentioning
confidence: 99%
“…[99][100][101][102] Increasing evidence also demonstrates that chondrocytes exhibit a self-defense mechanism that entails increasing anabolic activity in response to pathological processes, including the increased release of growth factors (i.e., BMP-2, Wnt) and synthesis of type II collagen and other extracellular matrix proteins. [103][104][105] This suggests that, although chon-drocytes undergo a self-protective mechanism, the elevation of anabolic molecules is not sufficient to neutralize upregulation of catabolic molecules, including TNF-␣, under pathological conditions. Highly specialized connective tissue, which consists of several types of collagens, proteoglycans, and other noncollagenous macromolecules, surrounds the chondrocytes.…”
Section: Pgrn In Osteoarthritismentioning
confidence: 99%
“…In addition, Takahito et al have suggested Wnt/β‐catenin signalling was a powerful stimulator of chondrocyte matrix catabolic action, leading to the degradation of cartilage matrix . Moreover, Zhang et al have shown that intermittent cyclic mechanical tension‐induced cartilaginous endplate degeneration may attribute to Wnt/β‐catenin signalling to some extent . In addition, Rac1 was reported to control β‐catenin phosphorylation and nuclear localization, providing novel target for therapeutic intervention of Wnt/β‐catenin pathway .…”
Section: Introductionmentioning
confidence: 99%
“…16 Moreover, Zhang et al have shown that intermittent cyclic mechanical tension-induced cartilaginous endplate degeneration may attribute to Wnt/β-catenin signalling to some extent. 20 In addition, Rac1 was reported to control β-catenin phosphorylation and nuclear localization, providing novel target for therapeutic intervention of Wnt/β-catenin pathway. 21 Herein, the intention of present study was to investigate the effect of Rac1 in the degeneration of cartilaginous endplate and potential relationship with Wnt/β-catenin pathway through IL-1β-induced endplate chondrocytes (EPCs) in vitro and rat annulus needle puncture models of IVDD in vivo.…”
mentioning
confidence: 99%